New Brunswick: Development of a Web-based orientation program and enhancing senior nurses' mentoring skills - Auffrey, Marise; Cormier-Daigle, Monique; Gagnon-Ouellette, Anne (Nursing Leadership, 2012)
This project to help new nurse recruits integrate into the hospital work environment had two components: the development of a new web-based orientation tool in French for new recruits and mentor training for more experienced nurses. The aim of the first component was to redesign delivery of the nursing orientation program by assessing individual needs of new recruits and developing "just in time" information sessions with online access and e-learning modules. The second component aimed to develop a voluntary mentorship training program for senior nurses that offered training on the role and responsibility of mentors. A total of 30 orientation modules were created as resources that could be adapted to the needs of each nursing unit and accessed online. Sixty nurse recruits used the programs. A mentor training program was developed, and 28 nurses were trained as mentors. The mentorship literature and guides, produced in French, will be a valuable resource for francophone nurses across Canada.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 4 - Identification des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
Le premier volet de l’étude globale « Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français », dressait un portrait des états de santé et des besoins de services des personnes ainées de ces deux quartiers. Le deuxième volet de l’étude portant sur l’identification des services de santé disponibles en français, a permis de répertorier 106 organismes des secteurs public, communautaire, privé à but lucratif et privé à but non lucratif offrant des services de santé en français à Saint-Boniface et à Saint-Vital. Les buts du présent volet sont 1) de repérer les ressources humaines bilingues pouvant servir les aînés en français au sein de ces mêmes organismes en prenant en considération tout le continuum de soins et 2) de mieux comprendre les pratiques actuelles et les défis entourant le recrutement, l’embauche et la rétention des professionnels pouvant offrir des services en français. Plus précisément, nous tenterons de déterminer le nombre et le pourcentage de professionnels pouvant offrir des services en français, d’identifier la nature des services offerts par ces professionnels bilingues, de définir les pratiques actuelles quant au recrutement et à l’embauche de personnel bilingue et de cerner les défis quant au jumelage des besoins des aînés avec les ressources humaines bilingues disponibles. Ainsi, nous disposerons d’un portrait des ressources humaines bilingues et des pratiques actuelles en matière de ressources humaines quant aux établissements désignés bilingues ou francophones, aux établissements de soins de longue durée et aux fournisseurs de soins à domicile à Saint-Boniface et à SaintVital.

Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 4 - Identification of current bilingual human ressources and human resource practices - de Moissac, Danielle; Ba, Halimatou; Roch-Gagné, Margaux; Gagné, M. (Université de Saint-Boniface, 2012)
The first part of the comprehensive study entitled “Improving St. Boniface and St. Vital Seniors’ Access to French-language Health Services,” provided an overview of the health status and service needs of seniors in these two neighborhoods. The second part, focused on identifying available French-language health services, listed 106 public, community, private forprofit and private not-for-profit and community organizations offering Frenchlanguage services in St. Boniface and St. Vital. The goals of this fourth part of the study are to: 1) identify bilingual human resources able to serve seniors in French within these organizations across the continuum of care and 2) better understand current practices and challenges in recruiting, hiring and retaining professionals who can offer French-language services. Specifically, we will attempt to determine the number and percentage of professionals who can offer French-language services, identify the nature of services offered by these bilingual professionals, identify current practices for recruiting and hiring bilingual staff and identify the challenges in matching the needs of seniors with bilingual human resources. This will provide us with an overview of current bilingual human resources and human resource practices in designated bilingual or Francophone facilities, long-term care facilities and home care providers in St. Boniface and St. Vital.
Voir le rapport en anglais à partir de la page 36 du PDF joint.

Défis associés à l’offre de services de santé et de services sociaux en français au Manitoba : perceptions des professionnels - de Moissac, Danielle; de Rocquigny, Janelle; Giasson, Florette; Tremblay, Cindy-Lynne; Aubin, Natalie; Charron, Marc; Allaire, Gratien (Reflets, 2012)
Les services de santé et les services sociaux en français ne sont accessibles qu’auprès d’un quart de la population francophone au Manitoba (de Moissac, 2011). Une pénurie de professionnels pouvant offrir des services en français est perçue comme un obstacle important pour les usagers qui recherchent ces services et pour les professionnels qui voudraient assurer un suivi en français pour leurs clients. Une hésitation à s’identifier comme francophone et un manque de connaissance des ressources disponibles en français contribuent-ils à cette perception de pénurie? Cet article traite des défis entourant l’offre de services de santé et de services sociaux en français au Manitoba et suggère des pistes de solutions. Mots-clés : disponibilité, accessibilité, minorité francophone, Manitoba, professionnels

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Compétences linguistiques et qualité de services. Argumentaire pour des services de soins de santé en français de qualité - Gauthier, Hubert; Reid, Marc-André (Conseil communauté en santé en français du Manitoba, 2012)
Citation suggérée par les auteurs: GAUTHIER, Hubert et REID, Marc-André. Compétences linguistiques et qualité de services, Argumentaire pour des services de soins de santé en français de qualité, Rapport pour le compte du Conseil communauté en santé du Manitoba, déposé en mars 2012, 46 pages.

Reference framework: Training for active offer of French-language health services - Lortie, L.ise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Cadre de référence pour la formation à l’offre active des services de santé en français (n°978-0-9879240-1-8) - Lortie, Lise; Lalonde, André. J. (Consortium national de formation en santé, 2012)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.